The Costs of Producing Biodiesel from Microalgae in the Asia-Pacific Region - Griffin, G.J.; Batten, D.F.; Beer, T.; Campbell, P.K. (International Journal of Renewable Energy Development, 2013)
Capital and operating cost estimates for converting microalgae to oil or biodiesel are compared. These cost comparisons are based on Australian locations, which are expected to fall at the lower end of the cost spectrum in the Asia-Pacific Region and other parts of the world.  It is assumed that microalgae are grown in a concentrated saltwater medium in raceway ponds, then are harvested, dewatered and the oil is extracted and converted to biodiesel by transesterification. The size of the desired pond system affects the number of potential locations due to constraints in resource availability. Cost estimates vary significantly due to differences in the assumed oil productivity, the harvesting equipment and the method of converting residual biomass to electric power. A comparison is made with recent cost estimates from other parts of the world, in which the expected costs of microalgae oil production from a number of publicly available sources lay between 0.34–31.0 USD/L.  The resulting cost estimates of between 1.37—2.66 USD/L are at the lower end of this scale, thereby confirming that Australia has the potential to be a low-cost producer of algal oil and biodiesel in the Asia-Pacific Region.  It was significant that, despite similar assumptions for the microalgae-to-oil process, cost estimates for the final biodiesel or oil price differed by a factor of 2.  This highlights the high degree of uncertainty in such economic predictions.